(3GdCMGOjK GdeNJGQIs - (3eMeO Hf YHO GdhGMO Hf CMeO Hf YHO GdQMef GdSYOj GdebOSj, VjGA GdOjf CHh YHO Gddg,J (B643 (3g` s ((3YHO GdQMef Hf eMeO Hf YHO GdZfi s)
(3ChdgG (B:s
(3Yf GHf YHGS bGd cGf bhe ef Cgd ecI CSdehG hcGfhG jSJNahf HESdGege aCNQLge GdeTQcjf jhe HOQ eYge s
(3BNQgG (B:s
(3Yf GHf YHGS ajeG jMSH Cf QShd Gddg Udi Gddg Ydjg hSde PcQ NOjLI HfJ NhjdO aPcQ eYfGg Je BNQ GdLRA s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs